Organizational Citizenship Behavior and Job Loyalty as Consequences of Job Satisfaction - Margrét Rúnarsdóttir 1990- (2018)
Determinants and consequences of job satisfaction continue to be a topic of reasonable interest within the field of psychology, both among researchers and practitioners. Employees who experience job satisfaction have a tendency to show job loyalty as well as organizational citizenship behaviors, which are altruist behaviors that go beyond formal requirements of one’s job. The aim of this study was to assess whether employees who experienced job satisfaction would show job loyalty and practice organizational citizenship behaviors as well as to examine whether employees in the public sector would differ from employees in the private sector on these variables. The participants of the study were 49 employees from three different companies in Iceland, two in the public sector and one in the private sector. Job satisfaction was measured with the Gallup Workplace Audit, job loyalty was measured with Meyer and Allen’s Model of Organizational Commitment and organizational citizenship behavior was measured with Degroot and Brownlee’s Organizational Citizenship Behavior Scale. Two out of three hypotheses were supported. Employees who scored high on job satisfaction also scored high on job loyalty but not organizational citizenship behavior and there was a significant difference between the public and private sector, with the private sector scoring higher on all three variables. Keywords: job satisfaction, job loyalty, organizational citizenship behavior Áhrifaþættir og afleiðingar starfsánægju eru hugtök sem hafa mikið verið rannsökuð innan sálfræðinnar. Rannsóknir sýna að starfsmenn sem upplifa starfsánægju hafa tilhneigingu til að sýna starfstryggð og þegnhegðun, en starfsmaður sem sýnir þegnhegðun gerir meira en af honum er ætlast til í starfi. Markmið þessarar rannsóknar var að kanna hvort starfsmenn sem upplifðu ánægju í starfi sýndu starfstryggð og framkvæmdu þegnhegðun en einnig að kanna hvort munur væri á þessum breytum með tilliti til þess hvort starfsmenn ynnu í einkageiranum eða þeim opinbera. Þátttakendur ...